No Textual Matter: Editors and Publishers of Early Colonial Spanish American Narrative (1493-1524). - Barrau, Oscar (International Journal of the Book, 2012)
Focused on a narrow idea of production that dismissed reception, critics and literary historians searched the origins of Spanish-American literature within authorial margins and the limits of the modern notion of the text. By neglecting the roles played by contemporary editors and publishers, not only have they missed the instrumental elements of book production, but ignored their mediating role with those who made literature possible: contemporary readers. This essay poses an alternative interpretation of the origins of Spanish American narrative by vindicating the materiality of the book, and of those behind it, and thus revisits the definition of literature outside the conventional margins of the text.